2014
DOI: 10.1021/nl404360k
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Porosity Hollow Nanoparticles for the Immunoprotection and Delivery of Nonhuman Enzymes

Abstract: Although enzymes of nonhuman origin have been studied for a variety of therapeutic and diagnostic applications, their use has been limited by the immune responses generated against them. The described dual-porosity hollow nanoparticle platform obviates immune attack on nonhuman enzymes paving the way to in vivo applications including enzyme-prodrug therapies and enzymatic depletion of tumor nutrients. This platform is manufactured with a versatile, scalable, and robust fabrication method. It efficiently encaps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 45 publications
0
76
0
1
Order By: Relevance
“…Nanocarriers help prevent drug degradation by evading the reticuloendothelial system (RES) and increase the bioavailability of the therapeutic agents at the target site [150][151][152]. In turn, adverse systemic side effects often decrease, while efficacy of the drug is enhanced.…”
Section: Nanotechnology For Combination Therapymentioning
confidence: 99%
“…Nanocarriers help prevent drug degradation by evading the reticuloendothelial system (RES) and increase the bioavailability of the therapeutic agents at the target site [150][151][152]. In turn, adverse systemic side effects often decrease, while efficacy of the drug is enhanced.…”
Section: Nanotechnology For Combination Therapymentioning
confidence: 99%
“…Various templates have been used for the control of the pore size, such as micelles of block copolymers, polymer nanoparticles, and emulsions. 43,86,151,167,267,305345 Here, we will introduce major examples of pore size control using these templates.…”
Section: Soft Template;mentioning
confidence: 99%
“…One example of HMSN synthesis using polystyrene nanoparticles as templates for pore and hollow structure formation. [467].…”
Section: Carbon Frameworkmentioning
confidence: 99%
“…The empty voids of HMSNs also offer flexibility in encapsulating enzymes to interact with diffusing species, thus forming biological nanoreactors. Ortac et al [467] demonstrated a polystyrene template approach to produce highly uniform HMSNs that were capable of being loaded with various enzymes and then protected by additional, controlled silica formation around the porous shell. The resulting nanoparticles boast a long circulation time due to the preserved enzymatic activity and capability to still interact with its target.…”
Section: Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation